2021
DOI: 10.2478/jccm-2021-0034
|View full text |Cite
|
Sign up to set email alerts
|

Survey of U.S. Critical Care Practitioners on Net Ultrafiltration Prescription and Practice Among Critically Ill Patients Receiving Kidney Replacement Therapy

Abstract: Introduction The current prescription and practice of net ultrafiltration among critically ill patients receiving kidney replacement therapy in the U.S. are unclear. Aim of the study To assess the attitudes of U.S. critical care practitioners on net ultrafiltration (UFNET) prescription and practice among critically ill patients with acute kidney injury treated with kidney replacement therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…We chose a UF NET rate of 0.5–1.5 mL/kg/hour in the restrictive arm because these UF NET rates are inclusive of the rates studied in the middle UF NET rate group in observational studies 11 13. We chose 2.0–5.0 mL/kg/hour in the liberal arm because these UF NET rates are also within the UF NET rate ranges studied in observational studies11 13 and surveys 6–9…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We chose a UF NET rate of 0.5–1.5 mL/kg/hour in the restrictive arm because these UF NET rates are inclusive of the rates studied in the middle UF NET rate group in observational studies 11 13. We chose 2.0–5.0 mL/kg/hour in the liberal arm because these UF NET rates are also within the UF NET rate ranges studied in observational studies11 13 and surveys 6–9…”
Section: Discussionmentioning
confidence: 99%
“…Second, we debated including a usual care arm in our trial. However, there are few published protocols for UF NET , and surveys show considerable variation in clinical practice 6–9. This makes it difficult to define what represents usual care for UF NET .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, observational studies have reported significant heterogeneity in RRT practice patterns within North America ( 15 , 16 ). Regarding FB management using ultrafiltration, an international survey has revealed significant practice variation ( 4 ), also regionally in North America ( 17 ) and Europe ( 18 ). Finally, surveys in the United Kingdom ( 19 ) and Australia and New Zealand (ANZ) ( 20 ) have demonstrated varying practices within nations.…”
mentioning
confidence: 99%